Umowa franchisingu w prawie państw europejskich - Mróz, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
A franchise agreement enables the creation of an autonomous enterprise. Simultaneously it provides for the avoidance of losses in early stages of business, since the brand is known and generally favourably regarded upon. In Europe it is of importance to create a transparent legal framework, taking the USA example, which will facilitate easy access to the franchise formula, whilst favouring globalization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 251-257